2015
DOI: 10.1007/s00289-015-1342-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of biodegradable polyurethane networks from carbonated soybean oil

Abstract: A series of renewable resource-based polyurethane networks (NIPUs) with potential application as biodegradable scaffold were prepared through a nonisocyanate methodology. For this purpose, carbonated soybean oil (CSBO) was reacted with amine curing agents composed of 3-aminopropyl-terminated poly (ethylene glycol) (ATPEG) and ethylene diamine (ED) at different weight ratios. CSBO was synthesized from epoxidized soybean oil and carbon dioxide gas at atmospheric pressure using an efficient catalyst system. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 47 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…The presence of these groups results in high hydrophilicity of those materials, which is a desirable property in the case of biodegradable materials. Moreover, the use of epoxidized unsaturated oils in cyclic carbonates production gives a potential to obtain biomaterial from renewable resources that should be easily resorbable by the living tissue [ 48 ]. NIPU materials develop rapidly, and there are already some reports on their progress, e.g., through electrospinning to fabricate mats for biomedical applications [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these groups results in high hydrophilicity of those materials, which is a desirable property in the case of biodegradable materials. Moreover, the use of epoxidized unsaturated oils in cyclic carbonates production gives a potential to obtain biomaterial from renewable resources that should be easily resorbable by the living tissue [ 48 ]. NIPU materials develop rapidly, and there are already some reports on their progress, e.g., through electrospinning to fabricate mats for biomedical applications [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a lot of efforts have been made to use renewable resources such as vegetable oils for the synthesis of polyols that can be used for ‘greener’ PUs prepration. 8 -11 Diisocyanates, which are used as basic raw materials for the production of the conventional addition PUs, are expensive, toxic, unstable and harmful to the environment and human health. The elimination of these materials and their replacement by natural and chemically stable compounds lead to the preparation of biodegradable, safe and environmentally friendly polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Jalilian and Yeganeh 8 prepared a series of renewable resource-based NIPU using carbonated soybean oil (CSBO), 3-aminopropyl-terminated poly (ethylene glycol) (ATPEG) and ethylene diamine (ED) at different weight ratios. Obtaind resuelts showed that hydrolytic degradation of NIPU increased with increasing ATPEG content as well as good cytocompatibility of the prepared PUs.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of cyclic carbonates from epoxides and CO 2 has been reviewed by North et al Most related works have been conducted with petrochemical‐derived epoxides such as ethylene oxide, propylene oxide, epichlorohydrin and styrene oxide . However, relatively few works have been devoted to the synthesis of cyclic carbonates from biorenewable resources such as vegetable oils . Cyclic fatty carbonates have been synthetized from epoxidized vegetable oils, which are obtained in turn from unsaturated natural oils with a high yield under mild conditions, using homogeneous or heterogeneous catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Reasearch about cyclic fatty carbonates has been mostly focused on carbonation of epoxidized soybean oil . Carbonated soybean has been obtained from the epoxidized oil by reaction with CO 2 , using tetrabutylammonium bromide (TBABr) at 110 °C and atmospheric pressure .…”
Section: Introductionmentioning
confidence: 99%